Fast Li‐ion Storage and Dynamics in TiO2 Nanoparticle Clusters Probed by Smart Scanning Electrochemical Cell Microscopy. Issue 9 (24th January 2023) - Tetteh, Emmanuel Batsa; Valavanis, Dimitrios; Daviddi, Enrico; Xu, Xiangdong; Santana Santos, Carla; Ventosa, Edgar; Martín‐Yerga, Daniel; Schuhmann, Wolfgang; Unwin, Patrick R.
Abstract: Anatase TiO2 is a promising material for Li‐ion (Li + ) batteries with fast charging capability. However, Li + (de)intercalation dynamics in TiO2 remain elusive and reported diffusivities span many orders of magnitude. Here, we develop a smart protocol for scanning electrochemical cell microscopy (SECCM) with in situ optical microscopy (OM) to enable the high‐throughput charge/discharge analysis of single TiO2 nanoparticle clusters. Directly probing active nanoparticles revealed that TiO2 with a size of ≈50 nm can store over 30 % of the theoretical capacity at an extremely fast charge/discharge rate of ≈100 C. This finding of fast Li + storage in TiO2 particles strengthens its potential for fast‐charging batteries. More generally, smart SECCM‐OM should find wide applications for high‐throughput electrochemical screening of nanostructured materials. Abstract : Smart scanning electrochemical cell microscopy (s‐SECCM), achieved through in situ interference reflection microscopy, enables the high throughput analysis of individual TiO2 nanoparticle clusters to estimate the Li + diffusivity and reveal the inherent fast charging capability of small TiO2 nanoparticle clusters.